Influence of Macromolecular Architecture on the Optical and Humidity-Sensing Properties of Poly(N,N-Dimethylacrylamide)-Based Block Copolymers - Katerina Lazarova (Polymers, 2018)
The influence of the macromolecular architecture of block copolymers containing poly(N,N-dimethyl acrylamide) (PDMA) on the optical characteristics and sensing properties of corresponding thin films is discussed. Series of hydrophilic PDMA-based copolymers of different chemical composition and chain architecture such as triblock, star-shaped, and branched were synthesized. The copolymers were characterized using conventional spectroscopic techniques as well as methods for characterization of copolymer macromolecular characteristics in solution, namely size-exclusion chromatography and static light scattering. Thin films of the copolymers of nanometer scale thickness were deposited on silicon substrates by the spin-coating method. The refractive index and extinction coefficient of the copolymer films were calculated from the reflectance spectra by using non-linear curve fitting methods and the composition-structure-optical properties relationships were evaluated. Humidity-sensing properties of the films were studied by measuring reflectance spectra of the films at a relative humidity range from 5 to 95%RH. The implementation of the copolymer films as optical sensors of humidity is justified and discussed.